Reorganization between preparatory and movement population responses in motor cortex - Gamaleldin F. Elsayed (Nature Portfolio, 2016)
Single neuron responses are highly complex and dynamic yet they are able to flexibly represent behaviour through their collective activity. Here the authors demonstrate that population activity patterns of motor cortex neurons are orthogonal during successive task epochs that are linked through a simple linear function.